Patients with Osteoporosis on Steroid Medication Tend to Sustain Subsequent Fractures - Hiwatashi, A.; Westesson, P.L. (American Journal of Neuroradiology, 2007)
BACKGROUND AND PURPOSE: Repeat fractures after percutaneous vertebroplasty can be seen in patients with osteoporotic compression fractures. The purpose of this study was to identify characteristics of patients with new fractures after vertebroplasty.MATERIALS AND METHODS: Fifty-five consecutive patients were treated with vertebroplasty for painful osteoporotic compression fractures at our institution. The charts and radiographic studies of all patients were retrospectively reviewed. Special attention was paid to patient age and sex, imaging studies, long-term use of steroid medication, and treatment for osteoporosis. We used logistic regression analysis and the Fisher exact test for statistical evaluation.RESULTS: Thirty-five patients were treated with vertebroplasty at one time and did not develop new fractures, whereas 20 patients returned with new fractures. Sixteen of 55 patients had been on steroid medication. The incidence of subsequent vertebral compression fractures after vertebroplasty in patients on long-term steroid therapy was 69% (11/16), compared with 23% (9/39) in those with primary osteoporosis (ie, those who were not on steroid therapy). There was a statistically significant association between use of steroids and new fractures (P < .01). No statistically significant difference was noted in patient age, sex, and medication for osteoporosis.CONCLUSION: Patients who are on long-term steroid medication have an elevated risk of developing new fractures after vertebroplasty.